Masjid di Mall: Integrasi Ruang Spiritual dalam Pusat Perbelanjaan Modern - Nurhasanah; Nur Hasan (Jurnal Ilmu Administrasi Publik, 2026)
The phenomenon of mosques in modern shopping malls demonstrates how urban public spaces are undergoing a transformation of meaning. Malls, often associated with consumerist lifestyles, now also accommodate spiritual needs. This article aims to analyze the role of mosques in malls from social, cultural, architectural, and economic perspectives. Using a descriptive qualitative approach through observation, interviews, and literature review, this study reveals that mosques in malls not only function as places of worship but also as symbols of religiosity, centers of da’wah, spaces for social interaction, and mall branding strategies. Their presence illustrates the hybridization between modernity and religiosity within the context of urban Indonesia. Keywords mosque, mall, public space, religiosity, modernity